Polyimide film, polyimide composition and display screen element
By using copolymers of specific chemical formulas in polyimide films and adjusting the molar ratio of dianhydride and dicarboxyl compounds, the problem of excessive decomposition of polyimide films during laser peeling is solved, and the effect of high transparency and heat resistance is achieved, which is suitable for the manufacturing of flexible OLED displays.
Patent Information
- Application Number
- CN202011620652.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-31
- Filing Date
- 2020-12-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-12-31
AI Technical Summary
In the manufacturing process of flexible organic light emitting diode (OLED) display screens, the polyimide film is prone to over-decomposition due to excessive energy intensity during laser peeling, resulting in a decrease in transmission and an increase in yellow index, affecting the transparency and optical performance of the display screen.
A polyamide-imide copolymer or polyimide film containing a specific chemical formula is used to ensure that the energy margin of the peeling laser reaches more than 30mj/cm2, and the heat resistance and transparency of the film are improved by adjusting the molar ratio of dianhydride and dicarboxyl compounds.
The polyimide film does not change color during laser peeling, ensures good peeling, and improves the heat resistance and transparency of the film, and is suitable for the manufacturing of high-performance flexible OLED displays.
Smart Images

Figure CN113121824B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polyimide film, in particular to a polyimide film that can be used as a substrate of a flexible display screen element, a polyimide composition for forming the polyimide film, and a display screen element using the polyimide composition. Background Art
[0002] With the recent increase in demand for flexible display screens, the development of flexible substrate materials is being actively carried out. For example, in a flexible organic light-emitting diode (OLED) display device, a polyimide film with excellent flexibility is used as the lower substrate of a thin film transistor (TFT). In the manufacturing process of a flexible organic light-emitting diode (OLED) display device, a polyimide film is first formed by coating and heat treating a carrier glass substrate with a polyimide varnish. Next, after a thin film transistor (TFT) and an organic light-emitting diode (OLED) cell are formed on the polyimide film, a laser with a wavelength of 308 nm is irradiated onto the back of the carrier glass substrate to separate the polyimide film from the carrier glass substrate. The above-mentioned peeling process using laser is called Laser LiftOff (LLO) process. Laser LiftOff (LLO) is a method of separating the glass substrate from the polyimide film by irradiating the interface of the polyimide film and the glass substrate with laser to decompose the polyimide attached to the glass substrate. When the energy intensity of the above-mentioned peeling laser is high, the polyimide film can be easily separated from the glass substrate, but the excessive decomposition of the polyimide film will cause the transmittance of the polyimide film to decrease and the yellow index to increase.
[0003] When an opaque colored polyimide film is used as a lower substrate in an upper light-emitting organic light-emitting diode (OLED) display, even if the yellow index of the polyimide film increases, it will not cause too serious a problem. However, in lower light-emitting organic light-emitting diode (OLED) displays, transparent displays, etc., because light needs to pass through the polyimide film (substrate), it is necessary to ensure the light transmittance of the polyimide film, that is, a higher transparency and a lower yellow index (Yellow Index). Therefore, in the laser lift-off (LLO) process, it is necessary to prevent the polyimide film from decreasing in transmittance and increasing in yellow index by appropriately adjusting the energy intensity of the lift-off laser. In addition, in a flexible organic light-emitting diode (OLED) using a 6th generation substrate (1500mm×1850mm), the adhesion of the polyimide film varies depending on the position of the substrate, and there is also a deviation in the energy intensity of the laser device, so it is necessary to control the energy intensity of the lift-off laser within a certain range to prevent the polyimide film from changing color and ensure that it can be lifted off well.
[0004] In addition, flexible organic light-emitting diodes (OLEDs) are usually manufactured through low-temperature polycrystalline silicon (LTPS) processes, and the temperature of low-temperature polycrystalline silicon (LTPS) processes is above 450°C. Therefore, the transparent polyimide film needs to have heat resistance at temperatures above 450°C. When the heat resistance of the polyimide film is insufficient, the polyimide film will decompose and the film will warp, resulting in a decrease in the yield of the low-temperature polycrystalline silicon (LTPS) process.
[0005] Prior art literature
[0006] Patent Literature
[0007] (Patent Document 1) Korean Patent Publication No. 10-2018-0047322 Summary of the invention
[0008] The object of the present invention is to provide a polyimide film that does not change color even when irradiated with a peeling laser having an energy intensity within a specific range and ensures that it can be peeled off well, a polyimide composition for forming the above-mentioned polyimide film, and a film manufacturing method using the above-mentioned polyimide composition.
[0009] Another object of the present invention is to provide a polyimide film having excellent heat resistance and transparency, a polyimide composition for forming the polyimide film, and a method for producing a film using the polyimide composition.
[0010] In order to achieve the above-mentioned object, the present invention provides a polyimide film, comprising one or more polyamide-imide copolymers represented by the following chemical formula 1 or polyimide represented by the following chemical formula 2, and the energy margin of the peeling laser is 30 mj / cm 2 above.
[0011]
Chemical formula 1
[0012]
[0013] In the above Chemical Formula 1, the ratio of n:m is 11:89 to 39:61, X is a tetravalent group having an aromatic ring structure, Y is a divalent group having an aromatic ring structure, and Z is a divalent group having an aromatic ring or an aliphatic ring structure.
[0014]
Chemical formula 2
[0015]
[0016] In the above Chemical Formula 2, the ratio of n:m is 21:79 to 94:6, X1 is a tetravalent group having an aromatic ring structure, Y1 is a divalent group having an aromatic ring structure, and Z1 is a tetravalent group having an aliphatic ring structure.
[0017] In addition, the present invention provides a polyimide composition comprising: (i) a copolymerized polyamide-imide represented by the above chemical formula 1; (ii) a polyimide represented by the above chemical formula 2; (iii) one or more polyimide components selected from the group consisting of the above precursors; and an organic solvent.
[0018] In addition, the present invention provides a display screen element, comprising at least one polyamide-imide copolymer represented by the above chemical formula 1 or a polyimide represented by the above chemical formula 2, and the energy margin of the peeling laser is 30 mj / cm 2 The above polyimide film.
[0019] The polyimide film to which the present invention is applied does not change color even when irradiated with a peeling laser having an energy intensity within a specific range, and ensures good peeling, and has excellent heat resistance and transparency. DETAILED DESCRIPTION
[0020] Next, the present invention will be described in detail. The present invention can be implemented in many different forms and is not limited to the specific embodiments described in the following.
[0021] The polyimide film applicable to one embodiment of the present invention may include a polyamide-imide copolymer represented by the following chemical formula 1 or a polyimide represented by the following chemical formula 2, and the energy margin of the stripping laser may be 30 mj / cm 2 above.
[0022]
Chemical formula 1
[0023]
[0024] In the above Chemical Formula 1, the ratio of n:m is 11:89 to 39:61, X is a tetravalent group having an aromatic ring structure, Y is a divalent group having an aromatic ring structure, and Z is a divalent group having an aromatic ring or an aliphatic ring structure.
[0025]
Chemical formula 2
[0026]
[0027] In the above Chemical Formula 2, the ratio of n:m is 21:79 to 94:6, X1 is a tetravalent group having an aromatic ring structure, Y1 is a divalent group having an aromatic ring structure, and Z1 is a tetravalent group having an aliphatic ring structure.
[0028] In the above chemical formula 1 and chemical formula 2, the structures of X and X1 can be independently selected from pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyl tetracarboxylic acid dianhydride (BPDA), 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6FDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,3,3',4-biphenyl tetracarboxylic acid dianhydride (a-BPDA), 2,3,3',4-biphenyl tetracarboxylic acid dianhydride (a-BPDA). dianhydride), 4,4'-oxydiphthalic anhydride (ODPA), 3,3',4,4'-diphenylsulfone-tetracarboxylic dianhydride (DSDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 4,4'-diphenylenedioxyphthalic anhydride (HQDA ... Anhydride), 5,5'-(9H-fluorene-9,9-substituted)bis(2-benzofuran-1,3-dione) (BPAF, 5,5'-(9H-Fluorene-9,9-diyl)bis(2-benzofuran-1,3-dione)) and mixtures thereof are derived from structures of aromatic dianhydride monomers, and specifically, structures derived from aromatic dianhydride monomers such as pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2,2'-bis(3,4-dicarboxylic)hexafluoropropane dianhydride (6FDA) and 5,5'-(9H-fluorene-9,9-substituted)bis(2-benzofuran-1,3-dione) (BPAF).
[0029] In the above chemical formula 1 and chemical formula 2, the structures of Y and Y1 can be independently selected from 2,2'-bis(trifluoromethyl)benzidine (TFMB), 3,3'-sulfonyldianiline, 4,4'-diaminodiphenylsulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, and bis[4-(4-aminophenoxy)phenyl]sulfone. The structures of aromatic diamine monomers include 4,4'-diaminobenzanilide, 4,4'-bis(4-aminophenyl)fluorine, 4-aminophenyl 4-aminobenzoate, 4,4'-diaminobenzanilide, 9,9-bis(4-aminophenyl)fluorine, and mixtures thereof. For example, as the diamine monomer, 2,2'-bis(trifluoromethyl)benzidine (TFMB) which is a fluorine-substituted aromatic diamine may be used in order to improve the transmittance of a polyimide film obtained by curing a polyimide precursor and reduce the yellow index.
[0030] In the chemical formula 1, the Z structure may be a structure derived from a dicarboxyl compound monomer such as p-Terephthaloyl chloride (TPC), isophthaloyl dichloride (IPC), 4,4'-oxybisbenzoyl chloride, and a mixture thereof.
[0031] In the above chemical formula 2, the Z1 structure can be 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (H-PMDA), octahydrodispiro[4,7-methanoisobenzofuran-5(3H), ), Dodecahydro-4,10:5,9-dimethano-1H,3H-naphtho[2,3-c:6,7-c']difuran-1,3,6,8-tetrahydrofuran (DMDA, Dodecahydro-4,10:5,9-dimethano-1H,3H-naphtho[2,3-c:6,7-c']difuran-1,3,6,8-tetrahydrofuran, ), bicyclooctanetetracarboxylic dianhydride (BODA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), and mixtures thereof are derived from the structure of dianhydride monomers having an aliphatic ring structure, specifically, structures such as 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (H-PMDA), octahydrobisspiro[4,7-methylisobenzofuran-5(3H)(CpODA), etc., which are derived from dianhydride monomers.
[0032] In the polyamide-imide represented by the above chemical formula 1, in order to increase the laser stripping energy margin of the film and improve the heat resistance, among all the structures (X+Z) derived from dianhydrides and dicarboxyl compounds, the molar ratio of the structure (Z) derived from the dicarboxyl compound is 11 to 39%, and the molar ratio of the structure (X) derived from the aromatic dianhydride is 61 to 89%. When the molar ratio of the structure (Z) derived from the above carboxyl compound is too low (less than 11%) or the molar ratio of the structure (X) derived from the aromatic is too high (more than 89%), the problem of reduced laser stripping energy margin may occur. In addition, when the molar ratio of the structure (Z) derived from the above carboxyl compound is too high (more than 39%) or the molar ratio of the structure (X) derived from the aromatic dianhydride is too low (less than 61%), the problem of reduced 1 wt% thermal decomposition temperature (Td1%) may occur.
[0033] In the polyimide represented by the above chemical formula 2, when the molar ratio (m) of the structure (Z1) derived from aliphatic dianhydride among all the structures (X1+Z1) derived from dianhydride is 6 to 9% and the molar ratio (n) of the structure (X1) derived from aromatic dianhydride is 21 to 94%, the peeling laser energy margin of the polyimide film can be increased and the heat resistance can be improved. When the molar ratio of the structure (Z1) derived from aliphatic dianhydride is too low (less than 6%) or the molar ratio of the structure (X1) derived from aromatic dianhydride is too high (more than 94%), the energy margin of laser peeling may be reduced. In addition, when the molar ratio of the structure (Z1) derived from aliphatic dianhydride is too high (more than 79%) or the molar ratio of the structure (X1) derived from aromatic dianhydride is too low (less than 21%), the heat resistance may be reduced due to the decrease in the 1 wt% thermal decomposition temperature (Td1%).
[0034] The polyimide represented by the above chemical formula 2 can be obtained by polymerizing a diamine monomer having a Y1 structure and a dianhydride monomer having structures X1 and Z1 using a general method. The polyamide-imide copolymer represented by the above chemical formula 1 can be obtained by polymerizing a diamine monomer having a Y structure, a dianhydride monomer having an X structure, and a dicarboxyl compound monomer having a Z structure using a general method.
[0035] A polyimide composition applicable to one embodiment of the present invention is used to form a polyimide film, comprising: (i) a copolymer polyamide-imide represented by the above chemical formula 1; (ii) a polyimide represented by the above chemical formula 2; (iii) one or more polyimide components selected from the group consisting of the above precursors; and an organic solvent. As a precursor of the polyamide-imide copolymer represented by the above chemical formula 1, a polyamide-imide-amic acid formed by polymerizing a diamine monomer having a Y structure, a dianhydride monomer having an X structure, and a dicarboxylic acid monomer having a Z structure can be taken as an example. As a precursor of the polyimide represented by the above chemical formula 2, a polyamic acid formed by reacting a diamine monomer having a Y1 structure and a dianhydride monomer having X1 and Z1 structures can be taken as an example.
[0036] As the organic solvent used in the above-mentioned polyimide composition, any organic solvent that can dissolve the copolyamide-imide represented by the above-mentioned Chemical Formula 1, the polyimide represented by the above-mentioned Chemical Formula 2 and their precursors can be used without particular limitation. For example, any one or more compounds selected from the group consisting of 1-methyl-2-pyrrolidone, N,N-dimethylpropionamide, diethylacetamide, N,N-dimethylacetamide (DMAc), 3-methoxy-N,N-dimethylpropionamide, 1-ethyl-2-pyrrolidone, N,N-dimethylisobutyramide, N,N-diethylformamide, N,N-dimethylformamide, N-methylformamide, N-ethylformamide, 1,3-dimethyl-2-imidazolidinone, r-butyrolactone, α-acetyllactone, β-propiolactone and δ-valerolactone can be used. The amount of the organic solvent used is 50 to 98 parts by weight, preferably 80 to 95 parts by weight, relative to 100 parts by weight of the copolyamide-imide represented by the chemical formula 1, the polyimide represented by the chemical formula 2, and their precursors. If the amount of the organic solvent used is too low, it may be difficult to coat due to high viscosity, while if the amount is too high, it is likely to produce streaks during the evaporation of the solvent.
[0037] The polyimide film applicable to the present invention can be manufactured by first coating the polyimide composition on a substrate such as a glass substrate, then heating the coated polyimide composition to a temperature of 350 to 550° C., then removing the organic solvent, and finally performing a polyimide forming reaction as required. The heating can be performed under a nitrogen environment for 5 minutes to 6 hours. The thickness of the polyimide film applicable to the present invention is generally 1 to 100 μm, specifically 1 to 50 μm.
[0038] The polyimide film applicable to the present invention can be decomposed at the contact surface with the glass substrate and peeled off from the glass substrate by irradiating a peeling laser with a wavelength of 308nm. When the energy intensity of the above-mentioned peeling laser is too low, it may lead to the problem that the polyimide film cannot be peeled off from the glass substrate. When the intensity of the peeling laser is too high, the polyimide film may be carbonized, resulting in problems such as a decrease in optical properties such as an increase in the yellow index. The energy margin of the peeling laser used when peeling the polyimide film applicable to the present invention is a peeling laser energy range that can maintain the optical properties of the polyimide film while peeling the polyimide film from the glass substrate, which is 30mj / cm 2In this specification, the range of peeling laser energy in which the polyimide film can be peeled off from the glass substrate and the yellow index value change (ΔYellowindex) before and after peeling (Laser Lift Off: LLO) of the polyimide film is 8 or less as shown in the following mathematical formula 1 is referred to as "energy margin". For example, when the energy density is 200mj / cm 2 The polyimide film with a thickness of 10±1μm can be peeled off at an energy density of 250mj / cm 2 When the yellow index value of the polyimide film changes to 8, the "energy margin" of the peeling laser is 50mj / cm 2 .
[0039]
Mathematical formula 1
[0040] Yellowness index value change = Yellowness index after stripping (LLO) - Yellowness index before stripping (LLO) ≤ 8
[0041] In order to increase the energy margin of the stripping laser, the polyimide film is required to absorb light with a wavelength of 308nm but have low sensitivity. Low sensitivity means low absorbance to light with a wavelength of 308nm. Under the above circumstances, the energy margin of the stripping laser can be increased. Although the polyimide film containing aliphatic or amide structure has low absorbance to light with a wavelength of 308nm, its heat resistance is lower than that of polyimide with aromatic structure. Because the temperature of general thin film transistor (TFT) engineering is above 450℃, the thermal decomposition temperature of 1% of the total weight of the thin film transistor (TFT) substrate material is required to reach above 450℃.
[0042] Transparent polyimide for thin film transistor (TFT) substrate requires high energy margin and heat resistance of the peeling laser. However, it is well known that there is a trade-off between the energy margin and heat resistance of the peeling laser, so it is difficult to produce a polyimide film with excellent both properties. The energy margin of the peeling laser for the polyimide film of the present invention is 30mj / cm 2As mentioned above, its peeling property is very good, and its thermal property, namely heat resistance, is also very good, with a 1 wt% thermal decomposition temperature (Td1%) of 450°C or above, specifically 460°C or above, and more specifically 470°C or above, based on a thickness of 10±1μm. Among them, the 1 wt% thermal decomposition temperature (Td1%) refers to the temperature at which the weight of the film decreases by 1 wt% due to thermal decomposition of the film when the film is subsequently heated, measured after the initial weight of the film is heated at 150°C for 30 minutes to remove moisture. In addition, when the polyimide film applicable to the present invention is formed into a film with a thickness of 200nm±50nm, the transmittance of light with a wavelength of 380nm is more than 10%, so its absorbance is low and a higher laser energy margin can be ensured.
[0043] Because the polyimide film applicable to the present invention has excellent thermal and optical properties, it can be used as a display screen element, specifically, it can be used as a substrate for a bottom-emitting or transparent organic light-emitting diode (OLED) panel, and especially because the energy margin of the stripping laser at a wavelength of 308nm is high, it can be applied to small, medium and large-area organic light-emitting diodes (OLEDs). Thus, the present invention provides a display screen element comprising the above-mentioned polyimide film.
[0044] Next, specific examples will be described in detail to help understand the present invention. However, the following examples are only illustrative of the present invention, and the present invention is not limited by the following examples. Next, unless otherwise clearly mentioned, % means weight %.
[0045] [Example 1 to Example 6] Production of copolyamide-imide compositions
[0046] While nitrogen is supplied to the reactor, N,N-dimethylacetamide (DMAc) is added as an organic solvent at room temperature, 2,2'-bis(trifluoromethyl)benzidine (TFMB) as a fluorine diamine monomer is dissolved in the organic solvent, and then 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (BPDA) or pyromellitic dianhydride (PMDA) as a dianhydride monomer and p-Terephthaloyl chloride (TPC) or isophthaloyl dichloride (IPC) as a dicarboxylic acid monomer are added in a molar ratio as shown in Table 1 below to react. After the reaction is completed, pyridine and acetic anhydride are added as a catalyst and a dehydrator, and then the temperature is raised to 70°C for 1 hour to react and then cooled to room temperature. The reaction was also put into a mixed solution of methanol and distilled water to obtain a solid precipitate. The obtained precipitate was washed with methanol and then dried in a vacuum oven at 80°C to obtain a copolyamide-imide. The obtained copolyamide-imide solid component was dispersed in an N,N-dimethylacetamide (DMAc) solution to produce a polyamide-imide composition.
[0047] [Example 7 to Example 11] Production of polyamic acid composition
[0048] While nitrogen is supplied to the reactor, N,N-dimethylacetamide (DMAc) is added as an organic solvent at room temperature, and then 2,2'-bis(trifluoromethyl)benzidine (TFMB) as a fluorine diamine monomer is dissolved in the above organic solvent. Then, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), octahydrobisspiro[4,7-methylisobenzofuran-5(3H) (CpODA) and 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA) as dianhydride monomers are added according to the molar ratio shown in Table 1 below, and then a reaction is carried out at room temperature for 24 hours to obtain a polyamic acid composition.
[0049]
Table 1
[0050]
[0051] (Unit: relative molar ratio relative to 1.00 mol of 2,2'-bis(trifluoromethyl)benzidine (TFMB))
[0052] [Comparative Examples 1 to 10] Production of polyimide composition
[0053] According to the composition shown in Table 2 below, 2,2'-bis(trifluoromethyl)benzidine (TFMB) and p-phenylenediamine (PPDA) were used as fluorinated diamine monomers, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), octahydrobisspiro[4,7-methylisobenzofuran-5(3H)] (CpODA) and 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA) were used as dianhydride monomers, and phthaloyl chloride ( TPC ), a polyimide composition was manufactured in the same manner as in Examples 1 to 11.
[0054]
Table 2
[0055]
[0056] (Unit: relative molar ratio relative to 1.00 mol of 2,2'-bis(trifluoromethyl)benzidine (TFMB) of Comparative Example 1)
[0057] [Examples A1-A11, Comparative Examples B1-B10] Production of polyimide film The polyamide-imide composition or polyimide precursor composition obtained in Examples 1 to 11 was coated on a glass substrate with a wet thickness of 400 μm, and then heated at 300° C. or 350° C. in a vacuum oven to produce a polyimide or copolyamide-imide film with a thickness of 10 μm. The physical properties of the produced polyimide film and copolyamide-imide film were evaluated by the following method, and the results are shown in Tables 3 and 4.
[0058] (1) Determination of thermal decomposition temperature (Td1%, unit: °C) :The thermal decomposition temperature (Td1%) was measured using TGA (TA instrument company, Discovery Model) in a nitrogen environment as follows. 10 mg of the sample was heated from 25°C to 150°C, and then the sample weight was measured after the water was removed by maintaining it at 150°C for 30 minutes. The temperature was then raised to 600°C at a rate of 10°C / min, and the temperature at which the sample weight decreased by 1% by weight was determined as Td1%.
[0059] (2) Determination of transmittance:The transmittance (T) of a 200nm thick polyimide film to a light of 380nm wavelength was measured using an optical measuring device Carry 4000 (Agilent). When measuring the transmittance, a glass substrate was used as a reference sample (Reference), and a glass substrate coated with a 200nm thick polyimide film was used as a sample (Sample) to measure its transmittance (%).
[0060] (3) Yellow Index (Yellow Index): The yellow index was measured using an optical measuring device COH-400 (Nippon Denshoku Corporation) using a C2 light source in accordance with American Society for Testing and Materials (ASTM) D1925.
[0061] (4) Energy margin assessment of lift-off laser : The laser lift-off device used was an AP System device, and a 308nm wavelength pulse laser was used at 100 to 250mj / cm 2 The polyimide film was irradiated with a laser overlap ratio of 80% within the laser density range to peel the film from the glass substrate. The yellow index (YI) value before and after peeling was measured, and the laser energy range where the difference in the yellow index before and after peeling, i.e., ΔYI, was less than 8 was taken as the glass energy margin of the polyimide film (unit: mj / cm 2 ).
[0062]
Table 3
[0063]
[0064]
Table 4
[0065]
[0066] As shown in Tables 3 and 4 above, when 2,2'-bis(trifluoromethyl)benzidine (TFMB) is used as a diamine monomer in a polyimide precursor and the content of the dicarboxylic compound, i.e., phthaloyl chloride (TPC), is increased in the total molar number of the dianhydride monomer and the dicarboxylic compound monomer (Examples 1 to 6), the transmittance at 308 nm will increase and the energy margin of laser stripping will also increase, but the heat resistance will decrease due to the relative decrease in the thermal decomposition temperature (Td1%). On the contrary, when the content of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) or pyromellitic dianhydride (PMDA) is 90% or 100% (Comparative Examples 1 to 4), although the heat resistance is excellent, the energy margin of laser stripping is reduced to less than 20, and when the content of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) is 50% (Comparative Example 5), although the energy margin of laser stripping is excellent, its heat resistance is reduced. When 2,2'-bis(trifluoromethyl)benzidine (TFMB) is used as a diamine monomer in a polyimide precursor and the content of octahydrobisspiro[4,7-methylisobenzofuran-5(3H)(CpODA) is increased in the overall molar number of the dianhydride monomer (Examples 7 to 11), although the energy margin of laser stripping increases, the heat resistance is reduced due to the relatively low thermal decomposition temperature (Td1%). On the contrary, when the content of octahydrobisspiro[4,7-methylisobenzofuran-5(3H)(CpODA) is 0.05% or 0% (Comparative Examples 6 and 8), the energy margin of laser stripping is less than 30, and when the content of octahydrobisspiro[4,7-methylisobenzofuran-5(3H)(CpODA) is 80% (Comparative Example 7), the thermal decomposition temperature (Td1%) is less than 450°C, which leads to a decrease in heat resistance.
[0067] In the above content, specific embodiments applicable to the present invention are described in detail, but the scope of the claims of the present invention is not limited thereby, but can be implemented in various forms within the scope of the appended claims.
Claims
1. A polyimide film, characterized in that: The present invention comprises at least one polyamide-imide copolymer represented by the following chemical formula 1 or a polyimide represented by the following chemical formula 2 and the energy margin of the lift-off laser is 30 mj / cm 2 above; 【Chemical formula 1】 In the above Chemical Formula 1, the ratio of n:m is 11:89 to 39:61, X is a tetravalent group having an aromatic ring structure, Y is a divalent group having an aromatic ring structure, and Z is a divalent group having an aromatic ring or an aliphatic ring structure. 【Chemical formula 2】 In the above Chemical Formula 2, the ratio of n:m is 21:79 to 94:6, X1 is a tetravalent group having an aromatic ring structure, Y1 is a divalent group having an aromatic ring structure, and Z1 is a tetravalent group having an aliphatic ring structure. The energy margin of the peeling laser refers to the energy range of the peeling laser in which the change in the yellow index value (ΔYellow index) of the polyimide film before and after peeling is 8 or less when the polyimide film is peeled from the substrate by laser irradiation. The X and X1 structures in the above chemical formula 1 and chemical formula 2 are independently selected from pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6FDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,3,3',4-biphenyltetracarboxylic dianhydride (a-BPDA), 4,4'-oxydiphthalic anhydride (O a structure derived from an aromatic dianhydride monomer selected from the group consisting of DPA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]malonic anhydride (BPADA), 4,4'-phenylenedioxydiphthalic anhydride (HQDA), 5,5'-(9H-fluorene-9,9-substituted)bis(2-benzofuran-1,3-dione) (BPAF), and mixtures thereof, The Y and Y1 structures in the above Chemical Formula 1 and Chemical Formula 2 are structures derived from a diamine monomer and are independently selected from the group consisting of 2,2'-bis(trifluoromethyl)benzidine (TFMB), 3,3'-sulfonyl dianiline, 4,4'-diaminodiphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, 3,4'-diaminodiphenyl ether, 4,4'-(1,3-phenylenedioxy)diphenylamine, 9,9-bis(4-amino-3-chlorophenyl)fluorene, 4-aminophenyl 4-aminobenzoate, 4,4'-diaminobenzanilide, 9,9-bis(4-aminophenyl)fluorene, and mixtures thereof. The Z structure in the above chemical formula 1 is a structure derived from a dicarboxyl compound monomer selected from the group consisting of terephthaloyl chloride, isophthaloyl chloride, 4,4'-oxydibenzoyl chloride and a mixture thereof. The Z1 structure in the above chemical formula 2 is a structure derived from an aliphatic cyclic dianhydride monomer selected from the group consisting of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (H-PMDA), octahydrobisspiro[4,7-methylisobenzofuran-5(3H)(CpODA), dodecahydro-4,10:5,9-dimethylbridge-1H,3H-naphtho[2,3-c:6,7-c']difuran-1,3,6,8-tetrahydrofuran (DMDA), bicyclooctanetetracarboxylic dianhydride (BODA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA) and mixtures thereof.
2. The polyimide film according to claim 1, characterized in that: The polyimide film has a transmittance of 10% or more to light having a wavelength of 380 nm.
3. The polyimide film according to claim 1, characterized in that: The 1 wt% thermal decomposition temperature (Td1%) of the polyimide film is 450°C or higher.
4. A polyimide composition, characterized in that: Include: (i) a copolyamide-imide represented by the above chemical formula 1; (ii) a polyimide represented by the above chemical formula 2; (iii) one or more polyimide components selected from the group consisting of the above precursors; and, Organic solvents; 【Chemical formula 1】 In the above Chemical Formula 1, the ratio of n:m is 11:89 to 39:61, X is a tetravalent group having an aromatic ring structure, Y is a divalent group having an aromatic ring structure, and Z is a divalent group having an aromatic ring or an aliphatic ring structure. 【Chemical formula 2】 In the above Chemical Formula 2, the ratio of n:m is 21:79 to 94:6, X1 is a tetravalent group having an aromatic ring structure, Y1 is a divalent group having an aromatic ring structure, and Z1 is a tetravalent group having an aliphatic ring structure. The X and X1 structures in the above chemical formula 1 and chemical formula 2 are independently selected from pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6FDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,3,3',4-biphenyltetracarboxylic dianhydride (a-BPDA), 4,4'-oxydiphthalic anhydride (O a structure derived from an aromatic dianhydride monomer selected from the group consisting of DPA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]malonic anhydride (BPADA), 4,4'-phenylenedioxydiphthalic anhydride (HQDA), 5,5'-(9H-fluorene-9,9-substituted)bis(2-benzofuran-1,3-dione) (BPAF), and mixtures thereof, The Y and Y1 structures in the above Chemical Formula 1 and Chemical Formula 2 are structures derived from a diamine monomer and are independently selected from the group consisting of 2,2'-bis(trifluoromethyl)benzidine (TFMB), 3,3'-sulfonyl dianiline, 4,4'-diaminodiphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, 3,4'-diaminodiphenyl ether, 4,4'-(1,3-phenylenedioxy)diphenylamine, 9,9-bis(4-amino-3-chlorophenyl)fluorene, 4-aminophenyl 4-aminobenzoate, 4,4'-diaminobenzanilide, 9,9-bis(4-aminophenyl)fluorene, and mixtures thereof. The Z structure in the above chemical formula 1 is a structure derived from a dicarboxyl compound monomer selected from the group consisting of terephthaloyl chloride, isophthaloyl chloride, 4,4'-oxydibenzoyl chloride and a mixture thereof. The Z1 structure in the above chemical formula 2 is a structure derived from an aliphatic cyclic dianhydride monomer selected from the group consisting of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (H-PMDA), octahydrobisspiro[4,7-methylisobenzofuran-5(3H)(CpODA), dodecahydro-4,10:5,9-dimethylbridge-1H,3H-naphtho[2,3-c:6,7-c']difuran-1,3,6,8-tetrahydrofuran (DMDA), bicyclooctanetetracarboxylic dianhydride (BODA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA) and mixtures thereof.
5. The polyimide composition according to claim 4, characterized in that: The above-mentioned organic solvent is any one or more compounds selected from the group consisting of 1-methyl-2-pyrrolidone, N,N-dimethylpropionamide, diethylacetamide, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropionamide, 1-ethyl-2-pyrrolidone, N,N-dimethylisobutyramide, N,N-diethylformamide, N,N-dimethylformamide, N-methylformamide, N-ethylformamide, 1,3-dimethyl-2-imidazolidinone, r-butyrolactone, α-acetyl lactone, β-propiolactone and δ-valerolactone.
6. A display screen element, characterized in that: The invention comprises one or more polyamide-imide copolymers represented by the following chemical formula 1 or polyimide represented by the following chemical formula 2, and the energy margin of the lift-off laser is 30 mj / cm 2 The above polyimide film, 【Chemical formula 1】 In the above Chemical Formula 1, the ratio of n:m is 11:89 to 39:61, X is a tetravalent group having an aromatic ring structure, Y is a divalent group having an aromatic ring structure, and Z is a divalent group having an aromatic ring or an aliphatic ring structure. 【Chemical formula 2】 In the above Chemical Formula 2, the ratio of n:m is 21:79 to 94:6, X1 is a tetravalent group having an aromatic ring structure, Y1 is a divalent group having an aromatic ring structure, and Z1 is a tetravalent group having an aliphatic ring structure. The energy margin of the peeling laser refers to the energy range of the peeling laser in which the change in the yellow index value (ΔYellow index) of the polyimide film before and after peeling is 8 or less when the polyimide film is peeled from the substrate by laser irradiation. The X and X1 structures in the above chemical formula 1 and chemical formula 2 are independently selected from pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6FDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,3,3',4-biphenyltetracarboxylic dianhydride (a-BPDA), 4,4'-oxydiphthalic anhydride (O a structure derived from an aromatic dianhydride monomer selected from the group consisting of DPA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]malonic anhydride (BPADA), 4,4'-phenylenedioxydiphthalic anhydride (HQDA), 5,5'-(9H-fluorene-9,9-substituted)bis(2-benzofuran-1,3-dione) (BPAF), and mixtures thereof, The Y and Y1 structures in the above Chemical Formula 1 and Chemical Formula 2 are structures derived from a diamine monomer and are independently selected from the group consisting of 2,2'-bis(trifluoromethyl)benzidine (TFMB), 3,3'-sulfonyl dianiline, 4,4'-diaminodiphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, 3,4'-diaminodiphenyl ether, 4,4'-(1,3-phenylenedioxy)diphenylamine, 9,9-bis(4-amino-3-chlorophenyl)fluorene, 4-aminophenyl 4-aminobenzoate, 4,4'-diaminobenzanilide, 9,9-bis(4-aminophenyl)fluorene, and mixtures thereof. The Z structure in the above chemical formula 1 is a structure derived from a dicarboxyl compound monomer selected from the group consisting of terephthaloyl chloride, isophthaloyl chloride, 4,4'-oxydibenzoyl chloride and a mixture thereof. The Z1 structure in the above chemical formula 2 is a structure derived from an aliphatic cyclic dianhydride monomer selected from the group consisting of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (H-PMDA), octahydrobisspiro[4,7-methylisobenzofuran-5(3H)(CpODA), dodecahydro-4,10:5,9-dimethylbridge-1H,3H-naphtho[2,3-c:6,7-c']difuran-1,3,6,8-tetrahydrofuran (DMDA), bicyclooctanetetracarboxylic dianhydride (BODA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA) and mixtures thereof.
Citation Information
Patent Citations
Composition for forming polyimide film and polyimide film prepared by using same
KR1020180047322A
Polyimide precursor, polyimide and manufacturing method of transparent polyimide film
CN107722268A